Prevalence and Determinants of Iron Deficiency Anemia in Adolescents Girls of Low Income Communities in Lahore - Hassan, Fatima; Salim, Shafya; Humayun, Ayesha (Annals of King Edward Medical University, 2017)
Abstract Background: Iron deficiency anemia (IDA) in adolescent girls has strong health implications during re-productive years. Current research aimed to assess prevalence and determinants of iron deficiency anemia in adolescent girls of low income families residing in semi urban communities of Lahore, Pakistan. Method: This cross sectional analytical study selected 116 unmarried adolescent girls between the ages of 13 – 19 years from low income families through convenience sampling from semi-urban communities. Dietary data was collected using 3 – day recall, whereas a self-constructed, structured questionnaire was used to collect data on socio-demographic factors. Hemoglobin and serum Ferritin levels were assessed along with an assessment of clinical signs and symptoms of folate and iron deficiency. Data was entered and analyzed using SPSS version 21. Results: IDA was present in 68.8% of adolescent girls, of which 40.2% were moderately (8 – 10 gm/dl) and 28.8% were mildly (10.9 – 11.9 gm/dl) anemic. Working status (p < 0.041), source of dietary iron (p < 0.001), frequency of heme iron consumption (p < 0.001), protein consumption/day (p < 0.001) and HEI score (p < 0.001) showed statistically significant association with IDA. Binary regression analysis showed frequency of heme iron consumption [AOR = 29.13, 95% CI (9.627 to 88.203)] and HEI score [AOR = 6.877, 95% CI (.065 to 44.405]) to be the most significantly associated determinant of IDA. Mean Hb level was also significantly different between working and nonworking adolescents (p = 0.001, 95% CI = -1.124 to -0.322). Significant mean difference in serum Ferritin levels between working and nonworking adolescents (p = 0.04 [95% CI = -21.89 to -0.50]) was also observed. 94% and 91% girls showed signs and symptoms of iron and folate deficiency respectively. How-ever BMI, age, educational status of the girls and their parents were not found to be associated with IDA. Conclusion: Prevalence of IDA was alarmingly high in adolescent girls of low socioeconomic class. Working status, source of dietary iron, frequency of heme iron consumption, protein consumption/day and HEI score were found to be determining anemia. Nutrition education targeting IDA is the need of the day to control and prevent this public health epidemic.